2015
DOI: 10.1016/j.ijmultiphaseflow.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Drag correlation for dilute and moderately dense fluid-particle systems using the lattice Boltzmann method

Abstract: This paper presents a numerical study of flow through static random assemblies of monodisperse, spherical particles. A lattice Boltzmann approach based on a two relaxation time collision operator is used to obtain reliable predictions of the particle drag by direct numerical simulation. From these predictions a closure law F (Re p , ϕ) of the drag force relationship to the bed density ϕ and the particle Reynolds number Re p is derived. The present study includes densities ϕ ranging from 0.01 to 0.35 with Re p … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 41 publications
10
51
0
Order By: Relevance
“…A similar study was reported in [23] for a Stokes flow around regular and random arrays of spherical solid obstacles. The effect of in a similar flow configuration was also of interest in [31]. Historically, the shift of the bounce-back boundary location with was first identified for channel flows [22].…”
Section: Open Flowmentioning
confidence: 99%
“…A similar study was reported in [23] for a Stokes flow around regular and random arrays of spherical solid obstacles. The effect of in a similar flow configuration was also of interest in [31]. Historically, the shift of the bounce-back boundary location with was first identified for channel flows [22].…”
Section: Open Flowmentioning
confidence: 99%
“…The total force acting on the sphere is the sum of the drag force F d , evaluated via Eq. (17) or (28), respectively, and the buoyancy force F b = π 6 D 3 a due to external forcing [5]. The total dimensionless force in forcing direction is then given as…”
Section: Force On Fixed Sphere In Stokes Flowmentioning
confidence: 99%
“…Originally, the TME metric [12] postulates a cost of less than 10 WU for a well-designed multigrid method. In [29] an extension to parallel textbook multigrid efficiency (parTME) is proposed by interlinking the classical algorithmic TME efficiency with efficient scalable implementations to (9) E parTME := t(n, n c ) t WU (n, n c ) = t(n, n c ) n c µ sm n .…”
Section: Textbook Multigrid Efficiencymentioning
confidence: 99%